2016
DOI: 10.1002/cbf.3226
|View full text |Cite
|
Sign up to set email alerts
|

Role of the p38 mitogen‐activated protein kinase signaling pathway in estrogen‐mediated protection following flap ischemia‐reperfusion injury

Abstract: Ischemia-reperfusion (I/R) injury often occurs during skin flap transplantation and results in tissue damage. Although estrogen treatment significantly alleviates this I/R injury-induced damage, the detailed molecular mechanism is not clear. In this study, a superficial epigastric artery flap I/R injury model was created in adult Wistar rats. Severe necrosis was observed in skin tissue after I/R injury. Histological examination of skin tissue revealed that I/R injury damages skin structure and results in neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The concentration of IL-6 in serum and the mRNA and protein concentrations of NF-κB and IL-6 in the flap tissues were significantly decreased. This is similar to previous experimental results (6,14). When the p38 MAPK signaling pathway was inhibited, the expression levels of inflammatory factors decreased, alleviating the inflammatory response in the flap.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The concentration of IL-6 in serum and the mRNA and protein concentrations of NF-κB and IL-6 in the flap tissues were significantly decreased. This is similar to previous experimental results (6,14). When the p38 MAPK signaling pathway was inhibited, the expression levels of inflammatory factors decreased, alleviating the inflammatory response in the flap.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that the MAPK pathways that promote occurrence and progression of inflammation were activated in ischemia-reperfusion injuries of a variety of tissues and organs (13). The p38 MAPK pathway, an important member in the MAPK family, played a major role in regulation of intracellular inflammatory response (14,15). In order to understand the role of p38 MAPK signaling pathway in flap ischemia-reperfusion injury and the underlying mechanism, a successfully constructed flap ischemia-reperfusion injury animal model was treated with SB202190, a specific inhibitor of the p38 MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is also notable that ERβ has been found to be more expressed in skin cells [61]. Also, the seven-transmembrane receptor, GPER30, has been reported to be involved in the effects of estrogens in human skin cells [62].…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact pathogenesis of cerebral IR injury remains unknown. Cumulative evidence suggests that numerous factors are involved in ischemic brain injury, including apoptosis, acid poisoning, ionic imbalance, excitotoxicity, oxidative stress, peri-infarct depolarization, nutritive stress, inflammation and reactive oxygen species (ROS) ( 5 12 ). Furthermore, numerous signaling pathways have been implicated in the pathogenesis of cerebral IR injury, including mitogen-activated protein kinases ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%